Arrays of infinite and discrete non-covalent interactions in the supramolecular adduct based upon trimeric perfluoro-ortho-phenylenemercury and 9-fluorenone. (16th August 2016) - Fisher, Steven P.; Reinheimer, Eric W.; Groeneman, Ryan H.
Graphical abstract: The synthesis and crystal structure of a new supramolecular adduct based upon ( o -C6 F4 Hg)3 and 9-fluorenone [( o -C6 F4 Hg)3 (9-fluorenone)2 ] was been realized. Observed within this complex is an array of supramolecular interactions ranging from Hg⋯O and Hg⋯C contacts to phenyl–phenyl and phenyl–perfluorophenyl interactions that produced an extended structure. Abstract: As a direct consequence of the accessibility to electrophilic Hg(II) atoms on its molecular surface coupled with its heightened electron-withdrawing properties, trimeric perfluoro- ortho -phenylenemercury, ( o -C6 F4 Hg)3, has exhibited a propensity to form supramolecular adducts with a wide array of substrates. Numerous examples of carbonyl-containing substrates as well as a number of polycyclic aromatics have been reported in the literature. However, the incorporation of these two organic functionalities within the same substrate has yet to be investigated in terms of complexation to ( o -C6 F4 Hg)3 . In this contribution, we report the synthesis, structural, and spectroscopic properties of a novel supramolecular adduct involving ( o -C6 F4 Hg)3 and 9-fluorenone [( o -C6 F4 Hg)3 (9-fluorenone)2 ]1 wherein the various non-covalent interactions observed are discussed. In particular, we address not only the interactions found between ( o -C6 F4 Hg)3 and 9-fluorenone, but also the interactions observed between 9-fluorenone molecules that produce either infinite or discrete assemblies perpetuated by C–H⋯O hydrogen bonds. Lastly, we will also discuss observed phenyl–phenyl and phenyl–perfluorophenyl interactions which form an extended molecular complex.